Modeling the crop growth - A review - SARGUN , KAUR; MOHAN , SINGH (MAUSAM, 2020)
Agriculture plays a key role in overall economic and social wellbeing of the specially developing countries. Now it is the right option to increase the quality and quantity of food production through the technological and managerial interventions like crop growth and yield prediction models. Various kinds of models such as Statistical, Mechanistic, Deterministic, Stochastic, Dynamic, Static, Simulations are in use for assessing and predicting crop growth and yield. Crop growth model is also a very effective tool for predicting possible impacts of climatic change on crop growth and yield. Crop growth models are useful for solving various practical problems in agriculture. Adequate human resource capacity has to be improved to develop and validate simulation models across the globe. This paper discusses various crop growth modeling approaches. Role of climate change in crop modeling and applications of crop growth models in agricultural activities are also discussed. A few successfully used crop growth models are discussed in detail.